2013
DOI: 10.1021/jp4067235
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mechanism and Synergetic Effects of Xanthone Derivatives as Noncompetitive α-Glucosidase Inhibitors: A Theoretical and Experimental Study

Abstract: Newly emerged xanthone derivatives have attracted considerable interests as a novel class of potent α-glucosidase inhibitors. To provide insights into the inhibitory and binding mechanisms of xanthone-based inhibitors toward α-glucosidase, we carried out experimental and theoretical studies on two typical xanthone derivatives, i.e., 1,3,7-trihydroxyxanthone and 1,3-dihydroxybenzoxanthone. The results indicate that these two xanthone derivatives belong to noncompetitive inhibitors and induce a loss in the α-hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 57 publications
5
28
0
Order By: Relevance
“…Thus, hydrogen bonds are formed via the hydroxyl groups of these GCGs. Notably, a similar phenomenon has been observed in other phenolic compounds such as xanthone derivatives, 23 resveratrol, and oxyresveratrol. 21 Moreover, more favorable hydrophobic interactions are formed between MF and MJ and α -glucosidase residues (Phe157, Phe158, Leu237, His239, His279 Phe300, and Ala278 for MF, and Phe157, Pro309, Leu237, His239, Leu218, His279, and Arg312 for MJ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, hydrogen bonds are formed via the hydroxyl groups of these GCGs. Notably, a similar phenomenon has been observed in other phenolic compounds such as xanthone derivatives, 23 resveratrol, and oxyresveratrol. 21 Moreover, more favorable hydrophobic interactions are formed between MF and MJ and α -glucosidase residues (Phe157, Phe158, Leu237, His239, His279 Phe300, and Ala278 for MF, and Phe157, Pro309, Leu237, His239, Leu218, His279, and Arg312 for MJ).…”
Section: Resultssupporting
confidence: 75%
“…As previous studies have suggested that the helix structure could be stabilized by targeting compounds with polyhydroxyl groups, 21, 23, 49 our CD results suggest that the helix structures were reduced with increasing concentrations of GA, MF, and MJ. Therefore, this implied that binding site 3 is not targeted by these GCGs.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…However, the nonsugar inhibitors of α -glucosidase have drawn the attention of researcher because of the limitations of sugar-mimicking inhibitors. Norathyriol and mangiferin have the same basic structure, the xanthone backbone, which is the molecular basis for α -glucosidase inhibition [11]. In the enzyme assays, norathyriol and mangiferin showed more potent inhibition of α -glucosidase than positive control (acarbose).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, complicated synergistic mechanisms are likely to be involved in many biological events in other investigations of mechanisms of α-glucosidase inhibition [30]. Liu et al demonstrated that a combination of inhibitors improves α-glucosidase inhibition [31]. They selected two typical xanthone derivatives (1,3,7-trihydroxyxanthone and 1,3-dihydroxybenzoxanthone) and observed their synergistic effect.…”
Section: Discussionmentioning
confidence: 99%